1992
DOI: 10.1001/jama.1992.03490210067037
|View full text |Cite
|
Sign up to set email alerts
|

Renal Function Change in Hypertensive Members of the Multiple Risk Factor Intervention Trial

Abstract: Effective blood pressure control was associated with stable or improving renal function in nonblacks but not in blacks. These findings emphasize the importance of blood pressure control to maintain adequate renal function in hypertensive white men and raise important questions about the relationship of pressure reduction and renal function change in blacks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0

Year Published

1993
1993
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(71 citation statements)
references
References 24 publications
5
66
0
Order By: Relevance
“…The Multiple Risk Factor Intervention Trial (MRFIT) study demonstrated that black people had a higher serum creatinine level for the same level of BP than white subjects. 34 From the therapeutic perspective it is important to consider drugs that reduce renal vascular resistance and glomerular pressure such as calcium channel blockers (CCB).…”
Section: National Health and Nutritional Survey (Nhanes)mentioning
confidence: 99%
“…The Multiple Risk Factor Intervention Trial (MRFIT) study demonstrated that black people had a higher serum creatinine level for the same level of BP than white subjects. 34 From the therapeutic perspective it is important to consider drugs that reduce renal vascular resistance and glomerular pressure such as calcium channel blockers (CCB).…”
Section: National Health and Nutritional Survey (Nhanes)mentioning
confidence: 99%
“…Hypertension in chronic kidney disease increases the risk of serious adverse outcomes, including renal failure, early development and accelerated progression of cardiovascular disease, and premature death (1)(2)(3). A number of randomized controlled trials have shown that antihypertensive treatment reduces cardiovascular mortality and morbidity and slows the progression of renal diseases (RD) (4)(5)(6). Furthermore, there is evidence that the benefit achieved is related to the extent to which blood pressure (BP) is lowered (1,(4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…11 In a subgroup analysis of 5524 MRFIT enrollees, despite a 5-mm Hg difference in diastolic blood pressure between those receiving usual care and special intervention, reciprocal creatinine slopes over 6 years in the two groups were the same. 22 Randomised controlled trials using only antihypertensive medications, however, provide the most direct and unbiased study design to address whether treatment of hypertension reduces the incidence of renal dysfunction among patients with non-malignant hypertension. Patients with diagnosed and undiagnosed renal disease should be evenly distributed in the treatment and the control group so that confounding from this important source is eliminated.…”
Section: Discussionmentioning
confidence: 99%
“…This was hypothesised a priori to be a possible source of heterogeneity among studies, as black subjects are believed to be particularly susceptible to renal damage from hypertension. 21,22 Information on whether and how patients with renal disease were excluded from entry into each trial was abstracted. Also noted was how new cases of renal dysfunction were defined in the paper presenting the main findings of each trial.…”
Section: Extraction Of Datamentioning
confidence: 99%